2022
DOI: 10.3390/biomedicines10123265
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation Alterations in Cancer Cells, Prognostic Value of Glycan Biomarkers and Their Potential as Novel Therapeutic Targets in Breast Cancer

Abstract: Although we are lately witnessing major improvements in breast cancer treatment and patient outcomes, there is still a significant proportion of patients not receiving efficient therapy. More precisely, patients with triple-negative breast cancer or any type of metastatic disease. Currently available prognostic and therapeutic biomarkers are not always applicable and oftentimes lack precision. The science of glycans is a relatively new scientific approach to better characterize malignant transformation and tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 118 publications
(159 reference statements)
0
4
0
Order By: Relevance
“…A relatively lower abundance of multi-antennary N-glycans was found as a characteristic of the luminal subtypes. The finding concerning the enhanced level of high-mannose glycans in breast cancer tissues, when compared with normal tissues associated with breast cancer diagnosis was reported 65 and can be connected with potential glycan-based targeted therapy or immunotherapy 66 in the future. The elevation of high-mannose N-glycans was also correlated with vascular invasion and lymph node involvement 35 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A relatively lower abundance of multi-antennary N-glycans was found as a characteristic of the luminal subtypes. The finding concerning the enhanced level of high-mannose glycans in breast cancer tissues, when compared with normal tissues associated with breast cancer diagnosis was reported 65 and can be connected with potential glycan-based targeted therapy or immunotherapy 66 in the future. The elevation of high-mannose N-glycans was also correlated with vascular invasion and lymph node involvement 35 .…”
Section: Discussionmentioning
confidence: 87%
“…While this comprehensive glycomic profiling technique has good clinical potential, further studies focusing on isomerism of sialic moieties could be crucial for understanding oncological consequences for different breast cancer cellular types. Recent research has shown that targeting N-glycan processing pathways may be a promising therapeutic approach for breast cancer 66 68 . In particular, inhibition of the enzyme N-acetylglucosaminyltransferase V (GnT-V) involved in the synthesis of certain N-glycans, has been shown to inhibit LVI and metastasis in breast cancer models 69 .…”
Section: Discussionmentioning
confidence: 99%
“…These inhibitors could induce receptor degradation, thereby blocking cell proliferation. This speculation is particularly intriguing given the growing interest in enzymes involved in glycosylation pathways as novel therapeutic targets in BC [37].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant glycosylation, a general characteristic feature of tumor cells, can lead to changes in both N-glycan and O-glycan structures, resulting in abnormal carbohydrate structures referred to as tumor-associated carbohydrates (TACAs). The specific types of glycans present in TACAs can vary depending on the cancer type and the glycosylation alterations occurring within the tumor cells [60]. Common alterations in cancer glycosylation include defects in glycan maturation, causing the expression of truncated glycan chains, as well as the expression of complex glycan motifs and loss of certain glycans [61].…”
Section: The Glycosylation Signature Of Metastatic Checkpointsmentioning
confidence: 99%